Legal and Political Challenges of Gender Equality and Crimes Against Women in Turkey: The Question of Istanbul Convention - Güneş-Ayata, Ayşe (Women & criminal justice, 2023)
Although the AKP government has made much legal and political progress on women’s rights, such as becoming the first government to ratify the Istanbul Convention, crimes against women in Turkey have dramatically risen in the last two decades. This is a notable step forward on women’s rights, in particular on violence against women. However, this step backwards for women’s rights with Turkey’s withdrawal from the Convention on 1 July 2021. This paper argues to what extent the shift from Europeanization to de-Europeanization and liberalism to conservatism in Turkey after 2011 directly affects its withdrawal from the Istanbul Convention. The first part of this paper analyses how the AKP government has taken many steps legally and politically on gender equality as part of Turkey’s Europeanization and EU accession process. The second part of this paper shows that, while many women’s rights organizations and society recognize that progress has been made, the AKP government’s withdrawal from the Istanbul Convention reveals Turkey’s transformation from liberalism to conservatism regarding women’s rights.